Ion Channels in Obesity: Pathophysiology and Potential Therapeutic Targets - Vasconcelos, Luiz H. C.; Souza, Iara L. L.; Pinheiro, Lílian S.; Silva, Bagnólia A. (Frontiers in Pharmacology, 2016)
Obesity is a multifactorial disease related to metabolic disorders and associated with genetic determinants. Currently, ion channels activity has been linked to many of these disorders, in addition to the central regulation of food intake, energetic balance, hormone release and response, as well as the adipocyte cell proliferation. Therefore, the objective of this work is to review the current knowledge about the influence of ion channels in obesity development. This review used different sources of literature (Google Scholar, PubMed, Scopus and Web of Science) to assess the role of ion channels in the pathophysiology of obesity. Ion channels present diverse key functions, such as the maintenance of physiological homeostasis and cell proliferation. Cell biology and pharmacological experimental evidences demonstrate that proliferating cells exhibit ion channel expression, conductance and electrical properties different from the resting cells. Thereby, a large variety of ion channels has been identified in the pathogenesis of obesity such as potassium, sodium, calcium and chloride channels, nicotinic acetylcholine receptor and transient receptor potential channels. The fundamental involvement of these channels on the generation of obesity leads to the progress in the knowledge about the mechanisms responsible for the obesity pathophysiology, consequently emerging as new targets for pharmacological modulation.